Characterization of constitutive and acid-induced outwardly rectifying chloride currents in immortalized mouse distal tubular cells - Valinsky, William C.; Touyz, Rhian M.; Shrier, Alvin (Biochimica et biophysica acta, 2017)
Thiazides block Na+ reabsorption while enhancing Ca2+ reabsorption in the kidney. As previously demonstrated in immortalized mouse distal convoluted tubule (MDCT) cells, chlorothiazide application induced a robust plasma membrane hyperpolarization, which increased Ca2+ uptake. This essential thiazide-induced hyperpolarization was prevented by the Cl− channel inhibitor 5-Nitro-2-(3-phenylpropylamino) benzoic acid (NPPB), implicating NPPB-sensitive Cl− channels, however the nature of these Cl− channels has been rarely described in the literature. Here we show that MDCT cells express a dominant, outwardly rectifying Cl− current at extracellular pH7.4. This constitutive Cl− current was more permeable to larger anions (Eisenman sequence I; I−>Br−≥Cl−) and was substantially inhibited by >100mM [Ca2+]o, which distinguished it from ClC-K2/barttin. Moreover, the constitutive Cl− current was blocked by NPPB, along with other Cl− channel inhibitors (4,4′-diisothiocyanatostilbene-2,2′-disulfonate, DIDS; flufenamic acid, FFA). Subjecting the MDCT cells to an acidic extracellular solution (pH<5.5) induced a substantially larger outwardly rectifying NPPB-sensitive Cl− current. This acid-induced Cl− current was also anion permeable (I−>Br−>Cl−), but was distinguished from the constitutive Cl− current by its rectification characteristics, ion sensitivities, and response to FFA. In addition, we have identified similar outwardly rectifying and acid-sensitive currents in immortalized cells from the inner medullary collecting duct (mIMCD-3 cells). Expression of an acid-induced Cl− current would be particularly relevant in the acidic IMCD (pH<5.5). To our knowledge, the properties of these Cl− currents are unique and provide the mechanisms to account for the Cl− efflux previously speculated to be present in MDCT cells. •MDCT cells express a dominant NPPB-sensitive Cl− current at pH7.4.•The constitutive Cl− current (pH7.4) does not arise from ClC-K2/barttin.•MDCT cells also express an acid-induced NPPB-sensitive Cl− current (pH<5.5).•Both the constitutive and acid-induced Cl− currents are unique.•mIMCD-3 cells express currents with similar biophysical properties.